AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN TRANSLATING POETRY - Intan Lutfiyani Khoerunisa (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This research aimed to find out students’ difficulties in translating poetry and its causes. In conducting the research, qualitative method and descriptive study are used. The data are taken from the students’ work, questionnaire and interview. The research is conducted to 15 third grade students of English Education Program at STKIP Garut. The research result shows that the students faced some difficulties in translating poetry. The students got difficulties in finding equivalent words from the source language into the target language, translating words which function as symbols, translating sentences with figures of speech, and the writing style of poetry which uses ungrammatical structures. Based on the result of the research, the researcher suggests that to translate poetry, the students have to enrich their knowledge about translation and poetry.